Millennial consumers’ acceptance of the sensory properties of gluten-free bread as predisposed by health and taste attitudes - De Kock, Henrietta Letitia (University of Pretoria, 2021)
Dissertation (MSc (Food Science))--University of Pretoria, 2020.